Curvature height and distance of MB canal of mandibular molar with Schneider angle and its comparison with canal access angle - Manjunath H. Malur; Anil Chandra (Elsevier, 2018)
Aim: To measure the proposed curvature height and distance of MB canal of mandibular molar with Schneider angle and its comparison with canal access angle both before and after instrumentation, and to compare among each other with multiple linear regression analysis. Methodology: One hundred human mandibular first and second molars were used for the study. After endodontic access, a size 10 k-file was placed in the mesiobuccal canal extending to the apical foramen and radiographs were taken by using Radiovisiography. Both Schneider and canal access angle with its respective linear counterpart (Curvature height and curvature distance) was measured and calculated by using PLANMECA romexis (Helsinki Finland) software connected to the Intraoral x-ray unit both before and after biomechanical preparation with mesiobuccal canal till size F2. Statistical analysis was done by using multiple linear regression analysis. Results: A significant difference was observed between before and after enlargement with respect to Schneider angle and Canal access angle with a t-value being (t = 11.0629, p < 0.05) (t = 10.5773, p < 0.05) for before and after enlargement of canals respectively. Percent of change is observed more with curvature height (29.62%) as compared with the curvature distance (8.87%) Conclusions: Schneider angle with its proposed curvature height and distance reduced after instrumentation. Whereas canal access angle decreased and its curvature height and distance have increased after instrumentation.